Stress and coping strategies among relatives of mentally ill in Ibadan metropolis, Oyo state, Nigeria (2022)
Mental illness of an individual does not just affect the patient, it may also be seen as a problem of the whole family. As primary care givers, families suffer from stress factors such as financial burdens, the neglect of other sibling and the interruption of the family routines. This work investigates the stress factors and coping strategies adopted by relatives of people living with mental illness in Ibadan Metropolis, Oyo state. The study adopted a cross-sectional research design involving 300 relatives of mentally ill individuals seen at the psychiatric unit of Ring Road State hospital, Ibadan. A purposive sampling was used to elicit information from respondents. Among other findings, it found that 59% of respondents were children of the mentally ill patients and 43% indicated that the emotional stress was the major stressor identified and creation of humour (29%) was the major coping strategy employed by the relatives. Furthermore, there were significant relationship between stressors, coping strategies and gender of the caregivers. The study recommends that the government health care providers and policy makers should organize public enlightenment programmes on mental health education. Health care providers should educate family members of mentally ill so as to enable them cope with stressors.